Assessment of the 3D geometrical effects on the DEMO divertor pumping efficiency. (May 2019) - Varoutis, S.; Igitkhanov, Yu.; Day, Chr.
Highlights: Study on the pumping efficiency of a 3D DEMO divertor configuration based on the size of inter-cassette gaps and the dome structure. The DIVGAS code is used to perform a sensitivity analysis of the DEMO divertor pumping efficiency. For the reference case of 20 mm gap width with the dome, the pumping efficiency is 9 times higher than for the case without the dome. The existence of dome results in the elimination of the neutral outflux towards the x-point and allows to achieve a neutral compression with consequent increase of pumping efficiency. Abstract: In the present work, a parametric analysis by using the DIVGAS code is performed in order to highlight the influence of the inter-cassette gaps and the existence of the dome on the overall pumping efficiency of the DEMO divertor. For this fundamental study, a 3D divertor configuration is chosen, in which deuterium neutral particles are assumed to penetrate the private flux region. The chosen incoming boundary conditions correspond to high-collisionality divertor operational conditions. It has been found that in the case for a divertor without a dome the particle losses through the separatrix are dominating and consequently the effect of 3D leakages on the pumping efficiency is small. For the reference case of 20 mm gap width with the dome and low capture coefficients, the pumping efficiency is 9 times higher than for the case without the dome. In general, the existence of dome results in the elimination of the outflux of neutrals towards the x-point and forces the neutrals to move towards the sub-divertor vicinity, finally achieving a neutral compression. It is shown that the dome provides a first order variation in pumping efficiency in comparison to the case of the divertor without the dome, while the gap leakages provide a second order variation, which seems to be more important when the dome is present.